Penerapan Problem Based Learning dalam Pengembangan Pemahaman Asmaul Husna pada Pembelajaran Pendidikan Agama Islam - Fadilawati, Agisna; Mazrur; Jennah, Rodhatul (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to describe the implementation of the Problem Based Learning (PBL) model in Islamic Religious Education (PAI) instruction on the topic of Asmaul Husna, specifically Al-Malik, Al-Quddus, and Al-‘Aziz—in Grade IV of SDN Pandan Sari. The research employs a descriptive qualitative approach, with data collected through classroom observations, interviews with PAI teachers and the school principal, as well as documentation of learning activities. The findings indicate that the application of PBL enhances students’ activeness, curiosity, and critical thinking skills in understanding the meanings and values of Asmaul Husna. Through problem identification, group discussion, problem-solving, and reflective activities, students are guided to internalize divine values contextually. The value of Al-Malik fosters responsibility and self-leadership, Al-Quddus strengthens awareness of physical and spiritual cleanliness, while Al-‘Aziz develops firmness and self-confidence. The school principal supports the implementation of PBL as it aligns with the school’s vision of strengthening religious character education. Therefore, PBL is proven to be an effective instructional strategy for instilling the values of Asmaul Husna in a meaningful and applicable manner in students’ daily lives.